The Use of Hyperbole and Metaphor in Musthafa Luthfi al-Manfaluthi’s Novel Rembulan Merah - Khairul Ihsan (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study explores the use of hyperbolic and metaphorical language styles in Rembulan Merah, a novel by Musthafa Luthfi al-Manfaluthi, through a stylistic analysis approach. Language plays a crucial role in literature, serving as a medium for authors to convey emotions, themes, and artistic expression. By analyzing the stylistic choices in this novel, the research aims to uncover the effects, meanings, and intentions behind the author's use of hyperbole and metaphor. The findings indicate that these stylistic devices significantly enhance the novel’s aesthetic and emotional appeal, making the narrative more engaging and impactful for readers. Hyperbole intensifies dramatic moments, emphasizing emotions and ideas in an exaggerated manner to create a lasting impression. Meanwhile, metaphor enriches descriptions, allowing abstract concepts to be conveyed through vivid and relatable imagery. Furthermore, these linguistic techniques contribute to the overall readability of the novel by making complex themes more accessible. The study highlights how al-Manfaluthi's writing style enables readers to immerse themselves in the story, experience the characters’ emotions, and visualize events with greater clarity. Additionally, the use of hyperbole and metaphor helps maintain narrative dynamism, preventing monotony and enhancing literary appreciation. Through this stylistic analysis, the research underscores the importance of language in shaping literary works and engaging readers.